Effect of Letrozole Based Intravaginal Device on Follicular Dynamics, Luteal Function and Fertility in Crossbred Cows Exhibiting Prolonged Oestrus - Aravind Suresh, Muthuvallukunnel; Pappu Unnikrishnan, Melitta; Jayakumar, Choppilil; Bibin Becha, Bahuleyan; Devassy Benjamin, Elavathinkal; Mohanan Syam Mohan, Kolamveettil (The Indian Journal of Animal Reproduction, 2025)
Eighteen cows exhibiting prolonged oestrus were randomly allotted to three groups (n=6 cows/group; Group I, II, III) and six cows with normal duration of oestrus formed Group IV. Letrozole impregnated (37.5mg) polyurethane sponge was used as intra-vaginal letrozole releasing device (IVLRD) and was inserted in Group I and II cows, whereas plain intra-vaginal device (IVD-P) was inserted in Group III and IV, on day 12 of observed oestrus. The IVD was removed on day 17 in all the groups; in Group II, 500 µg of cloprostenol was given parenterally, at the time of device removal. All the cows were artificially inseminated (AI) in the succeeding oestrus. Blood samples were collected for serum hormone assay and trans-rectal ultrasonography (TRUS) for ovarian dynamics were carried out in both the cycles. Pregnancy diagnosis by TRUS was carried out on day 45 of AI. Study revealed that letrozole, along with cloprostenol significantly reduced (p<0.05) the duration of oestrus (59.17 ± 3.27 vs 45.67 ± 4.11 h), persistence of dominant follicle (68.67 ± 3.00 vs 54.33 ± 4.14 h) and the suprabasal serum progesterone (P4) levels during the following oestrus (0.69 ± 0.09 vs 0.53 ± 0.06 ng/ mL), while serum P4 levels during dioestrus was significantly (p<0.05) increased (5.07 ± 0.34 vs 7.33 ± 0.26 ng/mL). Luteotropic effect of letrozole was also revealed in the study, as indicated by significantly higher serum P4 levels during late luteal phase in letrozole inserted cows.